(untitled) (Cadernos ESP, 2024)
To describe the sociodemographic, occupational and health profile of workers reported with Work-Related Mental Disorders (TMRT) belonging to the territory of the Litoral Leste/Jaguaribe/Ceará Health Superintendence (SLLJ), in the period from 2010 to 2022. Study epidemiological, ecological time series that used secondary data from TABNET. The 77 cases of Work-Related Mental Disorder reported during the analyzed period were included. There was a growing trend in notifications over the years, with greater frequency from 2019 onwards, the majority were female, mixed-race, the most recorded occupation was the category of education teachers and Community Agents health profession was the most reported among the accumulated cases, Aracati was the De-centralized Health Area with the most reported cases, the majority of which were not issued a Work Accident Report (CAT) and progressed to temporary incapacitation, in addition to the high number of omitted information in different notification fields. It is necessary to develop actions that promote monitoring of workers’ health, the information sent and the strengthening of lines of care related to workers’ mental health.